Analysing the Water-Energy-Food Nexus From a Polycentric Governance Perspective: Conceptual and Methodological Framework - Srigiri, Srinivasa Reddy; Dombrowsky, Ines (Frontiers in Environmental Science, 2022)
The Water-Energy-Food Nexus has emerged over the past decade as a useful concept to reduce trade-offs and increase synergies in promoting goals of water, energy and food securities. While WEF scholarship substantiates the biophysical interlinkages and calls for increased and effective coordination across sectors and levels, knowledge on conditions for effective coordination is still lacking. We aim to contribute to this understanding by conceptualising WEF nexus governance as a polycentric system from an analytical perspective based on the institutional analysis and development framework and the concept of Networks of Adjacent Action Situations (NAAS). The interdependence among transactions for pursuing WEF securities by actors in different action situations generates the need for coordination for changing or sustaining institutions, policy goals and policy instruments that guide actions leading to sustainable outcomes. Coordination is achieved through arrangements based on cooperation, coercion and competition. Coordination in complex social-ecological systems is unlikely to be achieved by a single governance mode but rather by synergistic combinations of governance modes. Particular coordination arrangements that emerge in a context depend on the distribution of authority, information and resources within and across interlinked decision-making centres. Further, integrating the political ecology based conceptualisations of power into the analytical framework extends the governance analysis to include the influence of power relations on coordination. Methodological innovation in delineating action situations and identifying the unit of analysis as well as integrating different sources and types of data is required to operationalise the conceptual framework.